Characterization of the innate immune response to Streptococcus pneumoniae infection in zebrafish. - Anni K Saralahti; Sanna-Kaisa E Harjula; Tommi Rantapero; Meri I E Uusi-Mäkelä; Mikko Kaasinen; Maiju Junno; Hannaleena Piippo; Matti Nykter; Olli Lohi; Samuli Rounioja; Mataleena Parikka; Mika Rämet (PLoS Genetics)
Streptococcus pneumoniae (pneumococcus) is one of the most frequent causes of pneumonia, sepsis and meningitis in humans, and an important cause of mortality among children and the elderly. We have previously reported the suitability of the zebrafish (Danio rerio) larval model for the study of the host-pathogen interactions in pneumococcal infection. In the present study, we characterized the zebrafish innate immune response to pneumococcus in detail through a whole-genome level transcriptome analysis and revealed a well-conserved response to this human pathogen in challenged larvae. In addition, to gain understanding of the genetic factors associated with the increased risk for severe pneumococcal infection in humans, we carried out a medium-scale forward genetic screen in zebrafish. In the screen, we identified a mutant fish line which showed compromised resistance to pneumococcus in the septic larval infection model. The transcriptome analysis of the mutant zebrafish larvae revealed deficient expression of a gene homologous for human C-reactive protein (CRP). Furthermore, knockout of one of the six zebrafish crp genes by CRISPR-Cas9 mutagenesis predisposed zebrafish larvae to a more severe pneumococcal infection, and the phenotype was further augmented by concomitant knockdown of a gene for another Crp isoform. This suggests a conserved function of C-reactive protein in anti-pneumococcal immunity in zebrafish. Altogether, this study highlights the similarity of the host response to pneumococcus in zebrafish and humans, gives evidence of the conserved role of C-reactive protein in the defense against pneumococcus, and suggests novel host genes associated with pneumococcal infection.